2017
DOI: 10.2147/cia.s113597
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry juice concentrate does not significantly decrease the incidence of acquired bacteriuria in female hip fracture patients receiving urine catheter: a double-blind randomized trial

Abstract: BackgroundUrinary tract infection (UTI) is a common complication among patients with hip fractures. Receiving an indwelling urinary catheter is a risk factor for developing UTIs. Treatment of symptomatic UTIs with antibiotics is expensive and can result in the development of antimicrobial resistance. Cranberries are thought to prevent UTI. There is no previous research on this potential effect in patients with hip fracture who receive urinary catheters.AimThe aim of this study is to investigate whether intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…There was no difference between the groups of patients with postoperative positive urine cultures at either day 5 or 14 days postoperatively (p = 0.975): 13 of 33 (39%) in the placebo group and 13 of 47 (28%) in the cranberry group (P=0.270) had a positive urine culture. However, this difference was not statistically significant (P=0.270)[51].Foxman et al concluded that patients undergoing elective gynecologic surgery involving urinary catheterization, the use of cranberry tablets during the postoperative period reduced the rate of UTI by at least a half; 15 of 80 patients (19%) for the intervention group in comparison to 30 of 80 patients (38%) for the placebo group with positive urine culture; (OR=0.38; 95% CI: 0.19, 0.79; p=0.008)[50].Educational and raising patient awareness approaches were discussed in eleven studies, five SRs[56,61- 64] and five RCTs[55,[57][58][59][60]. Meddings et al, who reviewed catheter discontinuation strategies for hospitalized patients and pooled their results of 7 seven trials, reported that the "stop order" intervention to prompt removal of unnecessary catheters reduced the duration of catheters in place by 1.06 days, and the use of either "reminders or stop orders" decreased the CA-UTI rate by 53%, (RR: 0.48; [0.28; 0.68]; p = 0.001)[56].…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…There was no difference between the groups of patients with postoperative positive urine cultures at either day 5 or 14 days postoperatively (p = 0.975): 13 of 33 (39%) in the placebo group and 13 of 47 (28%) in the cranberry group (P=0.270) had a positive urine culture. However, this difference was not statistically significant (P=0.270)[51].Foxman et al concluded that patients undergoing elective gynecologic surgery involving urinary catheterization, the use of cranberry tablets during the postoperative period reduced the rate of UTI by at least a half; 15 of 80 patients (19%) for the intervention group in comparison to 30 of 80 patients (38%) for the placebo group with positive urine culture; (OR=0.38; 95% CI: 0.19, 0.79; p=0.008)[50].Educational and raising patient awareness approaches were discussed in eleven studies, five SRs[56,61- 64] and five RCTs[55,[57][58][59][60]. Meddings et al, who reviewed catheter discontinuation strategies for hospitalized patients and pooled their results of 7 seven trials, reported that the "stop order" intervention to prompt removal of unnecessary catheters reduced the duration of catheters in place by 1.06 days, and the use of either "reminders or stop orders" decreased the CA-UTI rate by 53%, (RR: 0.48; [0.28; 0.68]; p = 0.001)[56].…”
mentioning
confidence: 78%
“…Both Foxman et al and Gunnarsson et al reviewed whether the prophylactic use of cranberry extract tablets during the postoperative period will reduce or even prevent the occurrence of CA-UTI[50,51]. In the study by Gunnarson et al, 227 female patients, aged 60 years and older, with hip fractures were randomized to either receive 550 mg of cranberry powder three times daily or placebo capsules daily until five days postoperatively[51].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The function of this urinary protein is not well understood, but it is associated with both cardiovascular and UT health and may influence overall UT host-microbiota interactions [317,318]. Trials investigating catheter-associated UTIs [319,320] already typically consider the unique microbiota profiles associated with these devices, but must now also consider the impact that cranberry materials may have on both initial patient UT microbiomes and on the development of both catheter biofilms and subsequent UTIs [63,321]. Clinical trials that investigate the concurrent use of cranberry materials and probiotics [313] must consider the possible prebiotic effects of cranberry oligosaccharides on both the existing microbiota and the provided probiotic organisms, as well as the possible colonization of the UT with the probiotic organisms [322,323].…”
Section: A New Paradigm For Uti Prevention With Cranberry Materialsmentioning
confidence: 99%
“…In women of reproductive age, cranberry lowered the number of clinical UTI episodes [47], reduced the risk of symptomatic UT infection [48] and decreased the risk of postoperative urinary tract infection in women undergoing benign gynecological surgery involving intraoperative catheterization [49,50], and in older women [51]. However, cranberry concentrate did not effectively prevent UT infections in female patients over 60 with hip fracture and an indwelling urinary catheter [52], nor in the therapy of bacteriuria plus pyuria among elderly women in a nursing home [53].…”
Section: Cranberry (Vaccinium Sp Especially Vaccinium Macrocarponmentioning
confidence: 99%